Effectiveness of landmark- and semi-landmark-based geometric morphometric to identify four species of Culex mosquitoes in Thailand - Chaiphongpachara, Tanawat; Laojun, Sedthapong (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This research aims to study the effectiveness of landmark- and semi-landmark-based geometric morphometric (LMSL) in the identification of four Culex vectors, namely, C. quinquefasciatus, C. visnui, C. sitiens, and C. whitmorei in Thailand and also compared the potential between LMSL and the landmark-based geometric morphometric method (LM). Materials and Methods: The overall size of the wing sample was estimated by the centroid size. Shape variables were computed as principal components of the “partial warp” calculated after generalized procrustes analysis of raw coordinates. Discriminant analysis of the canonical variables performed to explore the shape dissimilarity between Culex species has been shown as a factor map and to calculate the Mahalanobis distance. Size and shape differences based on pairwise Mahalanobis distances were tested using non-parametric methods (1,000 cycles) with Bonferroni correction at a p-value of <0.05. Results: A total of 120 individuals were used that were divided into 30 individuals per Culex species. The mean CS of C. sitiens had the largest wings followed by C. visnui, C. quinquefasciatus, and C. whitmorei in LM and LMSM. The patterns of statistical difference in CS of both methods were similar and wing shapes among Culex species were different based on a comparison of pairwise Mahalanobis distances (p < 0.05) in both methods. For the cross-validated reclassification test, LM provided Culex species separation ranging from 54% to 84% and 51% to 93% for LMSM. Conclusion: Thus, LMSM is another option to use for the identification in mosquito vectors that have a curved line on the wing specific to the species. J. Adv. Vet. Anim. Res., 6(3): 278-283, September 2019